PELATIHAN PEMBUATAN TALUT UNTUK MENAHANTANAH LONGSOR DI SELTER PENGUKHARJO WUKIRSARICANGKRINGAN SLEMAN - Imam Muchoyar,dan Bambang Sutjiroso, Pusoko Prapto, Bada Haryadi, (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2013)
The activities of skill trainning how to build the rock foundation in orderto defend the land fall down., in the shelter of Pengukharjo, Wukirsari,Cangkringan, Sleman,. This purpoused to increase the people ability in optionof masonry. They are able to understand step by step to make foundation ofhard rock and to understand the technology application of hard rock boundedwithout mortar. They can also to be improved the way of their life becameskilled labouerer specialy option Masonry job, who will get salary.This program is followed by more than 35 student from the people ofPengukharjo, Wukirsari, Cangkringan, Sleman, RT 3, RW, 3. Because this jobis non permanent job only, they don't have their land became their herintance,in other time they have to go back to their own land. They agree to build therock foundation up not using mortar. The skill training methode and to do thisjob are hold in the area straight away. Where are built foundation are permited.The result of this activities are the basic theory cant to be done togetherby all of the people,because they have to get salary from Kinahrejo, Kaliurang,as a seller of food, as a driver or rider motor car, sand and rock collector. Thisskill trainning to build rock foundation had been hold group by group, everyday. They are only 5- 10 worker. The Skill Trainning was begund at 8.00 PM,until 14,00 in the evening.every day. They can take a rest at 12.00, until 13.00afternoon. They could got money about 35.000 rupie every day, to do this job.They feel very glad and happy to do this trainning, because they could getmoney to continue their life.